International Marketing - Joshi, Rakesh Mohan (New Delhi Oxford University Press, 2014)
International Marketing, Second Edition is an exhaustive textbook designed to cater to the syllabi requirements of management students. Written in a student-friendly style, the book takes a detailed look at the domain of international marketing. This would give readers keen insights into overseas markets. The text provides comprehensive coverage of all the basic aspects of international marketing. Coupled with ample coverage of topics and a wide variety of examples, exhibits, and illustrations, the book goes on to develop managerial acumen in students. Beginning with an overview of international marketing concepts, the book discusses in detail the identification of emerging marketing opportunities, the environment, decision-making processes, and entry mode
Keywords: Marketing; Management; International Marketing